A new visual simulation tool for performance evaluation of MANET routing protocols - Sakib, Md. Sabbir Rahman; Saquib, Nazmus; Pathan, Al-Sakib Khan (Springer-Verlag, 2010)
A new user-friendly visual simulation tool; ViSim is presented. ViSim could be useful for researchers, students, teachers in their works, and for the demonstration of various wireless network scenarios on the computer screen. It could make the task of simulation more exciting and enhance the interest of the users without going into complex command-only text interface. Using our simulation tool, we measured the performance of several Mobile Ad-hoc Network (MANET) routing protocols. In this paper, we present the performance analysis of three prominent MANET routing protocols; DSDV, DSR, and AODV using ViSim. The details of various features of ViSim, brief descriptions of the selected routing protocols and their comparisons, details about the performed experiments, and gained results are also presented.